HS‐GC‐IMS detection of volatile organic compounds in Acacia honey powders under vacuum belt drying at different temperatures. Issue 8 (24th June 2021) - Feng, Duo; Wang, Jing; He, Yue; Ji, Xiao‐jiao; Tang, Hui; Dong, Yong‐mei; Yan, Wen‐jie
Abstract: Honey is a commodity of great nutritional value, but deep‐processed honey products are uncommon. Herein, we used vacuum belt dryer to dry Acacia honey at 60°C, 70°C, and 80°C, prepared it into powder, and analyzed its volatile compound differences. We established HS‐GC‐IMS method to detect the volatile organic compounds (VOCs) of these three Acacia honey powders (AHPs). In total, 77 peaks were detected, and 23 volatile compounds were identified, including eight aldehydes, six ketones, three furans, one alcohol, one phenol, one lactone, one ester, one acid, and one nitrile. Moreover, principal component analysis (PCA) and fingerprint similarity analysis based on the Euclidean distance distinguished the three heating temperature treatments. Clearly, it was concluded that there are significant differences in volatile substances at different tested temperatures, and when the AHP was incubated at 80°C, more volatile compounds were detected. Abstract : HS‐GC‐IMS detected volatile substances of honey powders. Honey powder with 80℃ contained more aldehydes, ketones, and furans. ​